Expectations and satisfaction of hospitality students with employment in hospitality industry - Ivkov, Milan; Simon, Viktorija; Tepavcevic, Jelena; Stojkovic, Ilinka (Turizam, 2020)
Education, complex skills and specialized knowledge of employees are crucial in industries such as hospitality industry. Students of hotel management in various ways try to acquire the experience necessary for employment, such as: professional practice, student exchange, attendance of specialized courses, etc. The importance of human resources both in hospitality industry and in all service industries is constantly growing. The main goal of this paper is to determine the expectations and satisfaction of hotel management students with employment in the hospitality industry. The survey was conducted among former and current students of hotel management of the Faculty of Sciences in Novi Sad. The results revealed statistically significant differences in responses. Theoretical and practical implications are discussed in order to help scholars and practitioners better understand this topic.